Comparison of electrochemical behaviour between La-free and La-containing CrMnFeNi HEA by Mott–Schottky analysis and EIS measurements. (17th February 2021) - Sun, Yipu; Lan, Aidong; Jin, Xi; Yang, Huijun; Qiao, Junwei
ABSTRACT: In this study, the electrochemical behaviour of CrMnFeNi and CrMnFeNiLa0.1 high-entropy alloys (HEAs) in 0.5 M H2 SO4 solutions was investigated. Potentiodynamic polarisation curves and electrochemical impedance spectroscopy (EIS) measurements showed that the addition of rare earth element lanthanum has a positive impact in enhancement of corrosion resistance capacity for CrMnFeNi HEAs. The potentiodynamic polarisation curves of the CrMnFeNi and CrMnFeNiLa0.1 alloys exhibit an extensive passive region ((Δ E >1000 mV). Mott–Schottky analysis showed that the donor densities decreased with the addition of La. The possible mechanism regarding the effect of inclusion of La on the dynamic of passivation process was discussed.